THE ROLE AND PLACE OF SOCIAL INSURANCE IN THE SYSTEM OF PUBLIC FINANCES OF UKRAINE - Козоріз , Григорій (Socio-economic relations in the digital society, 2019)
The article investigates the problems associated with the role and place of social insurance in the system of public finances, and the financial system as a whole. It is proved that the state is a key subject of the social insurance system and has a significant impact on entrepreneurs in this area, since it determines the level of reimbursements and the procedure for their deductions to state social funds. The influence of the system of social insurance on the state budget is established. It is revealed that the greatest correlation between the state budget and the social insurance system is manifested through the need to provide subsidies to the Pension Fund of Ukraine. The main stages of realization of the reform of the domestic social insurance system are analyzed, further perspectives of such transformations are found. The perspective directions of the development of the social insurance system, one of which is the state health insurance, are revealed.